THE EFFECTIVENESS OF THE RME METHOD TO IMPROVE STUDENTS' UNDERSTANDING OF THE CONCEPT OF A SQUARE - Ma'ruf, Abdul Hakim; Triyono, Ageng; Wibowo, Teguh (Journal of Authentic Research on Mathematics Education (JARME), 2024)
Students in class VII still have difficulty solving contextual problems related to the concept of a square. Through research, it will be shown that Realistic Mathematics Education(RME) and expository are more effective if it is based on students' post-test results after studying the concept of a square. The research objectives were achieved using a quasi-experimental method involving 2 groups of subjects, namely an experimental group of 33 students and a control group of 34 students. The subject group came from the class VII population at one of the junior high schools in Kebumen. The data analyzed is in the form of final semester exam results and posttest results collected using a test instrument in the form of 10 multiple choice questions. The data were analyzed using balance tests, normality tests, homogeneity tests, and effectiveness tests. Based on the results of the t-test and the hypothesis determined by the researcher, it can be shown that the application of the Realistic Mathematics Education(RME) method is more effective than the expository method. This conclusion is also strengthened by the mean value of the experimental group which is higher than the control group.